Rasgos emprendedores y la Orientación al Emprendimiento Sostenible (SEO) en las MYPES: el rol del género - Lazarte Aguirre, Luz Andrea (2025)
The current context in Peru presents a strong dependence on economic sectors that impact the environment, so the lack of sustainability in entrepreneurship aggravates environmental degradation and limits sustainable development. Despite being one of the most entrepreneurial countries in the world, the country faces the challenge of balancing economic growth with the preservation of ecosystems and social welfare. The motivation of this study lies in understanding how the traits of decision makers in Micro and Small Enterprises (MSEs) can contribute to orienting these enterprises towards more sustainable practices, through a dynamic capability of recent interest in the literature called Sustainable Entrepreneurial Orientation (SEO), which is essential for long-term sustainability and to generate a positive impact on the Peruvian economy and society. This study aimed to analyze the effect of the generic traits, explored in the entrepreneurial context, of the decision-maker on SEO and the effect of SEO on organizational performance, with gender as a moderator of this latter relationship. For this purpose, a quantitative research approach was used, with explanatory scope and nonexperimental design. The population and sample were represented by 121 MSES with reports according to the Global Reporting Initiative (GRI) standards in Peru. The proposed model was evaluated using questionnaires and the application of the least squares structural equations technique (PLS-SEM). It was found that, of the entrepreneurial traits of the decision maker, explicit power motives, consciousness, emotion regulation, entrepreneurial resilience, and self-efficacy encourage the emergence of SEO, as a precursor of sustainable entrepreneurship. Moreover, a significant correlation between SEO and organizational performance was found. Nevertheless, it is confirmed that gender does not moderate the previous relationship. Contributions to existing literature are obtained and practical applications are proposed for the Peruvian context, which shows high levels of involvement in entrepreneurship.